Air leakage measurement and analysis in duct type heating/cooling coils - (:unkn) unknown (My University, 2013)
The primary purpose of this study is to investigate the sources and rates of the air leakages in duct type heating cooling coils (DTHCC). In order to figure out the rate of air leakages in DTHCC, the tests have been primarily carried out on the reference duct type heating cooling coil (RDTHCC) as well as that, the RDTHCC has been tested on which the given enhancements have been implemented in the same order as follows: (1) only the corner's of RDTHCC have been sealed with a sealant, (2) only a rubber has been applied to the zones where casings and end-plates are joint and finally, (3) third step in which both enhancements are applied together. In this study, for the average test pressure of 400, 800, 1200, 1600, and 2000 Pa, air leakage rates of enhanced coils have been calculated and compared with the RDTHCC test results. Considering the maximum test pressure of 2000 Pa, the highest decrease in leakages can be seen with a 77,97% in the application where both enhancements carried out together, whereas the lowest decrease can be seen with a 26,07% in the enhancement step of only the corner's of RDTHCC have been sealed with a sealant. When only a rubber applied to the joints, the reduction is significant with a level of 62,56 %. © Sila Science.
Keywords: Air leakage; Cooling coil; DTHCC; Duct type; Heating coil